2000
DOI: 10.1021/bp0000048
|View full text |Cite
|
Sign up to set email alerts
|

Solid Substrate Fermentation of Monascus purpureus: Growth, Carbon Balance, and Consistency Analysis

Abstract: Solid substrate fermentation (SSF) of Monascus purpureus on rice is a promising new technology for obtaining natural pigments. However, before attempts can be made at maximizing pigment yield, all significant macroscopic compounds should be assayed. Here, Monascus purpureus has been grown on rice in batch mode, and the evolution of the main components, biomass, residual rice, O(2), CO(2), ethanol, acetic acid, and pigments, have been followed. This set of data, never previously studied for Monascus SSF, allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Monascus produces six primary pigments, which are two yellow pigments (monascin and ankaflavin), two orange pigments (monascorubrin and rubropunctatin), and two red pigments (monascorubramin and rubropunctamin). They constitute the color characteristic of angkak (Rosenblitt et al, 2000). The pigments obtained from Monascus have long been used to dye meat and fish products in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Monascus produces six primary pigments, which are two yellow pigments (monascin and ankaflavin), two orange pigments (monascorubrin and rubropunctatin), and two red pigments (monascorubramin and rubropunctamin). They constitute the color characteristic of angkak (Rosenblitt et al, 2000). The pigments obtained from Monascus have long been used to dye meat and fish products in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…During the culturing of Monascus CO 2 , ethanol and acetate are also produced. While working with SSF of rice, Rosenblitt et al (2000) showed that at the end of a 240 h fermentation, carbon balance was as follows: ca 23% of the carbon was converted to biomass, 35% to CO 2 , 15% to ethanol, 1% to acetic acid and 17% remained unused. The optimal temperature range for Monascus growth is 28-32°C, according to the registers of each species in strain banks, although this temperature varies depending on the strain between 25°C and 37°C (Lin, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Miyake et al, 1984ATCC 16362, CBS 285.34, ATCC 36927, DSM 1603 Monascus purpureus Went, deposited at CBS. Isolated from Angkak (fermented rice) Sheperd and Carels, 1979Rosenblitt et al 2000. ATCC 16365, CBS 109.07, ATCC 16426, IFO 4513, IMI 210765, NRRL 1596 Monascus purpureus Went, deposited at CBS.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings, submerged fermentation using Monascus sp. was developed, and the type of substrate employed was noted to be a crucial factor influencing Monascus growth, citrinin formation , and the cost of pigment production.…”
Section: Resultsmentioning
confidence: 99%